UMPSA strengthens collaboration with Cardiff Metropolitan University in Robotics and STEM Technology - Mimi Rabita, Abd Wahit (UMPSA, 2024)
PUTRAJAYA, 16 January 2024 - The collaboration between Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) and Cardiff Metropolitan University (CMU) will focus on leveraging robotics technology and Science, Technology, Engineering, and Mathematics (STEM) education to enhance learning opportunities among students.